Influence of Different Kinds of Polysaccharides on Crystal Growth of Calcium Oxalate in Microemulsion - Yue, Wenjin; Nie, Guangjun; Chen, Zhenxing; Li, Yanbin; Xu, Qianqian (Asian Journal of Chemistry, 2010)
Crystal growth of calcium oxalate in bulk aqueous solution, reverse microemulsion of p-octyl polyethylene glycol phenylether (OP)/iso-octyl alcohol (octyl alcohol)/cyclohexane/water and above microemulsion containing different kinds of polysaccharides, such as b-cyclodextrin, glucan, carboxyl methyl chitosan was studied. Calcium oxalate crystals were characterized by Fourier transform infrared spectroscopy, X-ray diffraction spectrum and scanning electron microscopy. The results indicated that different from manifold irregular crystal morphologies of calcium oxalate formed in bulk aqueous solution, more regular crystals such as calcium oxalate monohydrate, calcium oxalate dihydrate, calcium oxalate trihydrate existed in reverse microemulsion. The additive of b-cyclodextrin promoted crystal growth of calcium oxalate monohydrate to parallel with (101) face, while crystal growth of CaC2O4 preferentially oriented with the (020) face of calcium oxalate monohydrate after the addition of glucan. Carboxyl methyl chitosan promoted the formation of calcium oxalate trihydrate and prohibited the formation of calcium oxalate monohydrate, calcium oxalate dihydrate strongly. These facts suggested that different kinds of polysaccharides promote crystal growth of different calcium oxalate hydrate selectively. Furthermore, it could be concluded that carboxyl methyl chitosan may be the depressor of urinary stone in future.